An improved linearization technique for a class of quadratic 0-1 programming problems - He, Xiaozheng; Chen, Anthony; Chaovalitwongse, Wanpracha A.; Liu, Henry X. (Optimization letters, 2012)
The recent research on linearization techniques for solving 0-1 quadratic programming problems focuses on providing concise models and tightening constraint bounds. In this paper, we propose a computational enhancement for a linearization technique to make the linearized model much faster to solve. We investigate the computational performance of the proposed approach, by comparing it with other linearization techniques on a class of 0-1 quadratic programming problems. We can further speed up the proposed technique by heuristically tightening the constraint bounds, as demonstrated by solving the uncapacitated single allocation p -hub median problem using the Civil Aeronautics Board data.